Administrative justice fin de siáecle : early judicial standards of administrative conduct in Europe (1890-1910) - Della Cananea, Giacinto; Mannoni, Stefano (Oxford : Oxford University Press, 2021)
Administrative law permeates all area of law, and this series focuses on its role both regionally and globally. This volume focuses on the historical trajectory and developmental legacies of six legal systems from 1809-1910, and how they affect the administrative laws and legal institutions in place today.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 15, 2021).
Keywords: Administrative law -- Europe -- History -- 19th century; Administrative law -- Europe -- History -- 20th century; Comparative law